DEVELOPMENT OF WORKSHEET-BASED AUGMENTED REALITY (AR) MEDIA TO IMPROVE STUDENTS' LEARNING OUTCOMES ON THE RESPIRATORY SYSTEM MATERIAL IN CLASS XI IPA SMA NEGERI 5 PEMATANGSIANTAR - Giawa, Sedina; Siagian, Gunaria; Silaban, Winarto (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to develop and examine the feasibility and effectiveness of worksheet-based Augmented Reality (AR) learning media on the human respiratory system material for eleventh-grade science students at SMA Negeri 5 Pematangsiantar. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects were students of class XI IPA divided into experimental and control groups. Research instruments included expert validation sheets, student response questionnaires, and learning outcome tests (pretest and posttest). The validation results indicated that the developed AR-based worksheet media was feasible for instructional use. Student responses showed a practicality level of 86%, categorized as very practical. The analysis of learning outcomes using the Wilcoxon test revealed that the improvement in students’ learning outcomes in the experimental class was significantly higher than that in the control class, with a significance value of 0.000 < 0.05. These findings indicate that the use of worksheet-based AR learning media has a significant positive effect on students’ learning outcomes. Therefore, AR-based worksheet media can be utilized as an innovative alternative learning medium in Biology instruction, particularly for teaching the human respiratory system.